Social Media Language Trends and Formal Writing Competence in Indonesian: A Systematic Literature Review - Masriani Mery Rosmida Silalahi; Rani Rakasiwi (CV. INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the study: The rapid diffusion of social media has reshaped everyday language practices among Indonesian users, raising persistent pedagogical and sociolinguistic concerns about the erosion of formal writing competence in bahasa Indonesia baku. This systematic literature review synthesises empirical and theoretical evidence to determine (a) what social-media language trends have been identified in Indonesian contexts, (b) how these trends affect formal writing competence, (c) which competence sub-skills are most affected, (d) what positive and negative effects have been reported, and (e) which factors moderate the relationship between social-media language use and formal writing competence. Materials for Analysis: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) guidelines, a structured electronic search was conducted across Scopus, Web of Science, ERIC, DOAJ, Garuda (Garba Rujukan Digital), and Google Scholar for records published between January 2012 and June 2026. After de-duplication, title–abstract screening, and full-text eligibility assessment against predefined inclusion and exclusion criteria, thirty studies were retained. Data were extracted using a standardised coding sheet and synthesised through a thematic narrative approach organised around the five research questions. Results: The reviewed corpus documents a stable inventory of trends—slang (bahasa gaul), Indonesian–English code-mixing and code-switching, abbreviations and acronyms, non-standard affixation, orthographic play, and emoji use—concentrated on Instagram, TikTok, X (Twitter), and WhatsApp. The predominant, though not unanimous, finding is a negative association between habitual informal-digital language use and formal writing accuracy, most visibly in spelling (ejaan), punctuation, capitalisation, prepositions, affixation, and standard diction. Effects are bidirectional: alongside error transfer and register confusion, studies report vocabulary expansion, creativity, and writing fluency. Moderating variables—use intensity, digital literacy, register awareness, self-regulation, and cultural awareness—are frequently named but almost never statistically tested. Conclusions: Social-media language exerts a conditional rather than deterministic influence on formal Indonesian writing, with the direction of the effect contingent on measurement and design. The absence of true moderation testing constitutes the field's principal methodological gap and its clearest avenue for future confirmatory research.